TRANSLATION OF TREE NAMES IN UZBEK AND RUSSIAN LANGUAGES - Samigova Xushnuda Botirovna; Master Student: Tursunbayeva Dilnavoz (Galaxy International Interdisciplinary Research Journal, 2022)
In this article we continue to study English words by topic and their translation in Uzbek and Russian languages. As you may have guessed, today we will study the names of trees in English and their translation. Today we have no such a dictionary connected with thematic words like the names of trees.